Variables asociadas al nivel de gravedad de la preeclampsia en gestantes atendidas en emergencia del Hospital Regional de Loreto 2020 – 2022 - Ferreyra Guayabero, Delia (2024)
The objective was to determine the variables associated with the level of severity of preeclampsia in pregnant women treated in the emergency room of the Loreto Regional Hospital 2020 - 2022. The method was quantitative and the design was non-experimental, descriptive, retrospective, correlational. The population was made up of 338 medical records of pregnant women with preeclampsia and the sample consisted of 180 medical records. The technique was documentary review; The instruments: Demographic, social and clinical data sheet for pregnant women, Preeclampsia severity level classification registration data sheet. In the statistical analysis, SPSS software version 23.0 was used and, in the correlation, the chi-square test (χ²) with a significance level of 95% and an alpha value (α) ≤ 0.05 was used. Results: 59.4% were between 20 and 35 years old, 76.7% were housewives, 37.8% came from a peri-urban area, 45.0% received 4 to 6 prenatal control sessions, 61.1% responded no (greater than 18 months) for the short interpregnancy period, 43.3% presented familial preeclampsia and 48.3% presented other comorbidities. Regarding the level of severity of preeclampsia, 76.7% had mild preeclampsia. In conclusion, there is a significant association with age p = 0.004 (p < 5%), origin p = 0.026 (p < 5%); prenatal care p = 0.004 (p < 5%), short interpregnancy period p = 0.026 (p < 5%), pathological history p = 0.002 (p < 5%) and comorbidity p = 0.005 (p < 5%). Likewise, no association was found with occupation p = 0.216 (p < 5%).